[Students in costume for 'Dutch Dance' performed at annual Athletic Carnival.] - Frank Aston::::::photographer::: (1914)
Mar. 6, 1914. Students in costume for 'Dutch Dance' performed at annual Athletic Carnival. ('No. 2' -- Students with arms about each other's waists, one row) Same performers as in image published in Polytechnic J. 1914. Photo was taken outdoors but actual performance was given in the dining hall.